2020
DOI: 10.1053/j.gastro.2019.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Insulin-like Growth Factor 1 and Insulin-like Growth Factor Binding Protein 3 Associate With Risk of Colorectal Cancer Based on Serologic and Mendelian Randomization Analyses

Abstract: BACKGROUND & AIMS: Human studies examining associations between circulating levels of insulin-like growth factor 1 (IGF1) and insulin-like growth factor binding protein 3 (IGFBP3) and colorectal cancer risk have reported inconsistent results. We conducted complementary serologic and Mendelian randomization (MR) analyses to determine whether alterations in circulating levels of IGF1 or IGFBP3 are associated with colorectal cancer development. METHODS: Serum levels of IGF1 were measured in blood samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 46 publications
4
87
0
Order By: Relevance
“…The findings of a likely causal effect of IGF-I in prostate cancer development may be due to its role in activating signalling pathways which regulate cell proliferation and apoptosis 2 . The positive relationship between IGF-I and incident prostate cancer observed is consistent with previous epidemiological evidence 4 , as well as associations observed with other cancers including breast and colorectal [35][36][37] . Further genetic epidemiology including fine mapping may help elucidate exactly by which mechanism variation at the IGF1 locus associates with risk prostate and some other cancers.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of a likely causal effect of IGF-I in prostate cancer development may be due to its role in activating signalling pathways which regulate cell proliferation and apoptosis 2 . The positive relationship between IGF-I and incident prostate cancer observed is consistent with previous epidemiological evidence 4 , as well as associations observed with other cancers including breast and colorectal [35][36][37] . Further genetic epidemiology including fine mapping may help elucidate exactly by which mechanism variation at the IGF1 locus associates with risk prostate and some other cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding for colorectal cancer confirm those of a previous MR study which showed an OR of colorectal cancer of 1.08 (95% CI 1.03-1.12) per one SD increment of genetically-predicted IGF-1 levels. 6 That study further showed that directly measured serum IGF-1 levels were associated with increased risk of all colorectal tumor subsites, including proximal colon, distal colon, and rectal cancer. 6 Possible mechanisms underlying the increased colorectal cancer risk include direct actions of IGF-1 on cell growth or indirect effects via for example insulin resistance and elevated insulin levels.…”
Section: Discussionmentioning
confidence: 87%
“…6 That study further showed that directly measured serum IGF-1 levels were associated with increased risk of all colorectal tumor subsites, including proximal colon, distal colon, and rectal cancer. 6 Possible mechanisms underlying the increased colorectal cancer risk include direct actions of IGF-1 on cell growth or indirect effects via for example insulin resistance and elevated insulin levels. 25 The present MR results for IGF-1 and breast cancer based on BCAC data are similar to those obtained from another MR study also based on BCAC data which showed an OR of 1.05 (95% CI 1.01-1.10) per 5 nmol/L increase of genetically predicted IGF-1 levels based on 265 SNPs associated with serum IGF-1 levels in women.…”
Section: Discussionmentioning
confidence: 87%
“…We then used the ICCs to recalibrate the multivariable HR estimates for regression dilution. 25,26 To assess the linearity in the associations of circulating liver function markers with CRC risk, we performed restricted cubic spline analysis with four knots and calculated the likelihood ratio test by comparing the model with only the linear term of these markers to the model with both the linear and the cubic spline terms.…”
Section: Discussionmentioning
confidence: 99%